Stimulasi Perkembangan Bahasa Anak Usia Dini melalui Metode Bercerita Interaktif di Lembaga PAUD - Lisnida Yanti; Syamsiah Depalina (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study aims to examine the effectiveness of an interactive storytelling method supported by visual media in enhancing young children's language skills and character development. The research employs a qualitative approach, collecting data through observation, interviews, and descriptive analysis of learning practices in early childhood education institutions (PAUD). The findings indicate that the use of visual media and active interaction from parents and teachers significantly enriches vocabulary, improves listening skills, and supports children's social- emotional and overall character development. These results underscore the crucial role of parents and visual media in the language stimulation and character-building process for early childhood, aligning with language development theories and social constructivism as foundational principles for effective learning approaches.